Clinical manifestations of rotavirus diarrhea in the outpatient clinic of Cipto Mangunkusumo Hospital, Jakarta - Teny Tjitrasari; Agus Firmansyah; Imral Chair (Indonesian Pediatric Society, 2005)
Background Rotavirus is one of the most common cause of acutediarrhea among hospitalized and pediatric outpatients, especiallythose aged 6-24 months. Data of hospitalized children showed thatrotavirus causes severe diarrhea, but data of outpatient children inIndonesia, especially at Cipto Mangunkusumo Hospital Jakarta, islimited.Objective To characterize the clinical manifestations of rotavirusdiarrhea in the pediatric outpatient clinic at Cipto MangunkusumoHospital Jakarta.Methods This was a cross-sectional study, done in July 2003 –March 2004. Stool specimens were collected from patients aged6-24 months with diarrhea and tested for rotavirus by ELISA.Result Of the 98 children enrolled, 35 (35.7%) children excretedrotavirus. Rotavirus diarrhea was seen in 43.8% of children aged6-11 months, of whom 37.0% of them were undernourished. Maleswere affected 1.4 times as much as females. The clinical manifes-tations were passage of diarrheic stools more than 10 times a day(58.3%), mild-moderate dehydration (55.8%), cough (51.9%),rhinorhea (46.0%), vomiting (44.8%), fever (41.1%), yellow stools(38.9%), and mucus in the stool (20.0%). The highest prevalenceof rotavirus diarrhea was identified in the combination of diarrhea,fever, vomiting and cough/rhinorrhea (55.3%). Stool analysis re-vealed that the prevalence of rotavirus diarrhea among childrenwith fat malabsorption, lactose malabsorption, and stool leukocyteof +2 were 50.0%, 46.7% and 33.9%, respectively.Conclusion The prevalence of rotavirus diarrhea in the pediatricoutpatient clinic of Cipto Mangunkusumo Hospital, Jakarta was35.7%. The highest prevalence of rotavirus diarrhea was identifiedin the combination of diarrhea, fever, vomiting and cough/rhinorhea(55.3%)